Understanding the determinants of infant and under-five mortality rates: a multivariate decomposition analysis of Demographic and Health Surveys in Ghana, 2003, 2008 and 2014. Issue 4 (9th July 2019) - Dwomoh, Duah; Amuasi, Susan; Agyabeng, Kofi; Incoom, Gabriel; Alhassan, Yakubu; Yawson, Alfred Edwin
Abstract : Introduction: Despite the decline in infant and under-five mortality rates since the last decade, Ghana did not meet the millennium development goal (MDG) 4 target. To implement effective interventions that could fast-track progress towards achieving the sustainable development goal 3 in 2030, factors contributing to the decline in child mortality throughout the MDG period and which factor(s) has/have been consistent in affecting child survival in the last decade need to be understood. Methods: This study used Demographic and Health Surveys (DHS) from 2003, 2008 and 2014 and data from World Bank Development Indicators (2000–2018). We employed modified Poisson with robust SE and multivariate decomposition approach to assess risk factors of child mortality using DHS data from 2003, 2008 and 2014. Penalised regression was used assess the effect of 25 country-level contextual factors on child survival. Results: The risk of infant mortality is approximately five times higher among mothers who had multiple births compared with mothers who had single birth over the last decade (adjusted relative risk 4.6, 95% CI 3.2 to 6.6, p<0.001). An increase in the annual percentage of female labour force participation (FLFP) is associated with the reduction of approximately 10 and 18 infant and under-five annual deaths per 1000 live births, respectively. Conclusions: This study found that multiple births and shorter birth spacing are associated with increased risk of infant and under-five deaths over the last decade. Increased in FLFP, and the proportion of children sleeping under bed-net are associated with reduced risk of both infants and under-five deaths.